107k views
0 votes
What is the correct formula for the Ksp of the reaction MgF2(s) – Mg2+ (aq) + 2F (aq)?

Ksp = [Mg2+][F]
Ksp =[Mg2+][F]2
Ksp = 2[Mg2+][F]
Ksp = [Mg2+][F]

User Tomd
by
5.1k points

2 Answers

1 vote

Answer:

Ksp = [Mg2+]3 × [PO43-]2

Step-by-step explanation:

edge 2021

User Brtgmaden
by
5.6k points
0 votes

Answer:

Ksp = [Mg₂⁺][F⁻]²

Step-by-step explanation:

Ksp is the equilibrium constant for a solid dissolving in an aqueous solution. The equilibrium constant for a reaction is always products over reactants.

MgF₂ (s) ⇒ Mg₂⁺(aq) + 2F⁻(aq)

The equilibrium constant would be K = [Mg₂⁺][F⁻]². Since MgF₂ is solid, it is not included in the equilibrium expression.

Therefore, Ksp would be the same as the equilibrium constant.

Ksp = [Mg₂⁺][F⁻]²

Hope this helps.

User Yasir
by
5.0k points